2022
DOI: 10.3390/biomedicines10123272
|View full text |Cite
|
Sign up to set email alerts
|

Ruminococcaceae_UCG-013 Promotes Obesity Resistance in Mice

Abstract: Alterations in the gut microbiome have been linked to obesity and type 2 diabetes, in epidemiologic studies and studies of fecal transfer effects in germ-free mice. Here, we aimed to identify the effects of specific gut microbes on the phenotype of mice fed a high-fat diet (HFD). After eight weeks of HFD feeding, male C57BL/6J mice in the HFD group ranking in the upper and lower quartiles for body weight gain were considered obese prone and obese resistant, respectively. 16S rRNA gene sequencing was used to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…Mueller et al [40] studied that after metformin treatment, the relative abundance of Ruminococcus torque group increased and improved overweight/obese adults, which means that Ruminococcus torques can alleviate obesity. Feng et al [41] also proved that Ruminococcaceae can alleviate obesity. Studies have shown that Ruminococcaceae_UCG-013 is positively correlated with serum HDL-C levels and negatively correlated with serum TC, TG and LDL-C levels, and can be identi ed as the most important biomarker for reducing obesity.…”
Section: Discussionmentioning
confidence: 97%
“…Mueller et al [40] studied that after metformin treatment, the relative abundance of Ruminococcus torque group increased and improved overweight/obese adults, which means that Ruminococcus torques can alleviate obesity. Feng et al [41] also proved that Ruminococcaceae can alleviate obesity. Studies have shown that Ruminococcaceae_UCG-013 is positively correlated with serum HDL-C levels and negatively correlated with serum TC, TG and LDL-C levels, and can be identi ed as the most important biomarker for reducing obesity.…”
Section: Discussionmentioning
confidence: 97%
“…The Genus Ruminococcaceae UCG003 belongs to the Ruminococcaceae family, and many bacteria in this family are known to be general butyrate-producing bacteria [44]. The effect of Ruminococcaceae UCG003 on IVDD may be mediated by butyrate, as shown by Jia et al [45].…”
Section: Discussionmentioning
confidence: 98%
“…These bacteria are able to utilize cellulose and other components of plant cell walls to produce organic acids and gases through fermentation, providing energy and nutrients to the host. These bacteria in the human gut are associated with intestinal health and metabolism ( 31 ).…”
Section: Discussionmentioning
confidence: 99%